2016
DOI: 10.1097/md.0000000000005593
|View full text |Cite
|
Sign up to set email alerts
|

Association of RAGE gene Gly82Ser polymorphism with coronary artery disease and ischemic stroke

Abstract: Background:The receptor for advanced glycosylation end products (RAGE) has been widely linked to diabetic atherosclerosis, but its effects on coronary artery disease (CAD) and ischemic stroke (IS) remain controversial. The Gly82Ser polymorphism is located in the ligand-binding V domain of RAGE, suggesting a possible influence of this variant on RAGE function. The aim of the present study is to clarify the association between the RAGE Gly82Ser polymorphism and susceptibility to CAD and IS.Methods:Eligible studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…For example, extensive studies in the Chinese Han population suggested that the rs2070600 SNP was significantly associated with increased risk of all-cause mortality and acute myocardial infarction (MI) (118). Ma and colleagues performed a meta-analysis of 16 eligible studies reporting on rs2070600 SNP and CVD; they reported an association between this SNP and coronary artery disease (CAD) and ischemic stroke (IS) in the Chinese population, but not in non-Chinese populations (119). Until studies examining larger groups of subjects are examined to fully test this AGER SNP and potential relationships to CVD, studies of these specific populations in China may, therefore, shed light on mechanisms of RAGE-dependent predilections to CVD.…”
Section: Rage and Diaph1 And Snps-deepening The Connections To Human mentioning
confidence: 99%
“…For example, extensive studies in the Chinese Han population suggested that the rs2070600 SNP was significantly associated with increased risk of all-cause mortality and acute myocardial infarction (MI) (118). Ma and colleagues performed a meta-analysis of 16 eligible studies reporting on rs2070600 SNP and CVD; they reported an association between this SNP and coronary artery disease (CAD) and ischemic stroke (IS) in the Chinese population, but not in non-Chinese populations (119). Until studies examining larger groups of subjects are examined to fully test this AGER SNP and potential relationships to CVD, studies of these specific populations in China may, therefore, shed light on mechanisms of RAGE-dependent predilections to CVD.…”
Section: Rage and Diaph1 And Snps-deepening The Connections To Human mentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) play important roles in gene regulation; more than half of human genes are known to be regulated by miRNAs. miRNAs are also involved in numerous pathological pathways/process, such as the inflammatory response (1,2) and cancer development (3,4), as well as in the formation/development of ischemic stroke (IS) (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding RAGE and HMGB1 are highly polymorphic, and more than twenty single nucleotide polymorphisms (SNPs) have been investigated [ 22 , 23 ]. Despite a large panel of RAGE and vascular disease-related genetic association studies, it remains unclear whether individuals possessing certain alleles are more susceptible to IS due their main or joint effects [ 24 - 27 ]. Therefore, we performed a case-control study to determine whether the variants of RAGE and HMGB1 genes are associated with IS susceptibility in a relatively large southern Chinese population.…”
Section: Introductionmentioning
confidence: 99%